Návrh a zhodnocení financování investičního záměru - Pěnkavová, Karolína (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Diplomová práce se zabývá investiční výstavbou podnikové prodejny a degustačního sklepa ve společnosti Vinné sklepy Valtice, a. s. Je zde posouzena finanční situace společnosti, zhodnocení efektivnosti investice a srovnání konkrétních nabídek bankovních institucí. Stěžejní částí práce posuzuje na základě získaných informací, zda lze realizovat investiční záměr.

Master´s thesis deals with project that invests into construction of retail store and tasting cellar of company Vinné sklepy Valtice, a. s. Thesis contains the assessment of company’s financial position, evaluation of investment effectiveness and the comparison of individual offers from bank institutions. The main part of thesis contains analysis of consolidated data. Based on this information has been decided whether to proceed with investment or not and then proposed an appropriate plan for financing of this project.
Proposal and Evaluating for Funding Investment Project
Keywords: Finanční analýza; investice; investiční projekt; financování; bankovní úvěr.; Financial analysis; investment; investment project; financing; bank loan.